Pendampingan Pengembangan Modul Ajar dan Asesmen Berbasis Literasi Numerasi melalui Workshop Kolaboratif di SMK Negeri 3 Kota Blitar - Kristiani Kristiani; Cicik Pramesti; Sita Khoirin Nisa; Riki Suliana RS; Suryanti Suryanti; Ayu Silvi Lisvian Sari; M. Khafid Irsyadi (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
Numeracy is not merely the ability to perform calculations, rather, it is the capacity to understand, interpret, and communicate mathematically rich information in real world contexts. Strengthening numeracy is not the sole responsibility of mathematics teachers. It requires collaboration across all subject areas. National and international assessments consistently indicate that the numeracy skills of Indonesian students have not improved significantly and, in some cases, have shown a declining trend. Preliminary observations revealed that, although SMK Negeri 3 Blitar had conducted activities to raise awareness of numeracy literacy, it lacked established best practices for developing numeracy-based teaching modules and assessments. Consequently, a collaborative workshop was organized at SMK Negeri 3 Blitar to provide guidance in the development of these materials. This initiative was carried out in collaboration with the Blitar Campus (PSDKU) of Universitas PGRI Adi Buana Surabaya and aimed to enhance teachers’ understanding of numeracy while supporting the production of numeracy based teaching modules and assessments. The program employed a collaborative workshop approach consisting of four stages: preparation, implementation, evaluation, and reporting. A total of forty four teachers from various subject areas participated in the two day event, which included presentations, sharing sessions, and group based practical activities focused on developing teaching modules and assessments. The evaluation indicated that 84% of participants achieved a high level of understanding of fundamental numeracy literacy concepts, and all groups successfully produced numeracy based teaching modules and assessments. Nevertheless, participants’ ability to design assessments still requires further improvement, as only 39% reached the high-proficiency category. Therefore, continued assistance through more intensive hands on training is recommended.